Household food security and children’s food consumption diversity in the different agroecological regions in West Java, Indonesia. - Dewi, Puspita; Khomsan, Ali; Dwiriani, Cesilia Meti; Sukandar, Dadang (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction: Food security is essential for a country's development. This is emphasized in the SDG's goal of zero hunger. Food security means that a household can consistently access sufficient quantity and quality food. Geographical location influences access to food. This research aims to analyze food security and diversity in different agroecological regions (highlands and coastal) in West Java. Methods: The design used in this research is a cross-sectional study. This research was conducted in Cianjur Regency (highlands) and Karawang Regency (coastal) West Java Province, Indonesia. The population in this study were households with children aged 12-24 months. The total number of households sampled in this study was 154. Data on children's food consumption was collected using the 1x24-hour food recall method, while other data was collected by interviews using questionnaires. Results: As many as 63.6% of subjects in the highlands were aged 12-18 months and 49.4% in coastal area. Maternal education in the highlands was higher than in the coastal (p<0.05). Family members of ≤4 people were more common on the coastal (p<0.05). As many as 62.3% of households in the highlands and 81.8% in the coastal areas allocate food expenditure <60% of total spending. There is no difference in household food security in the highlands and the coastal (p>0.05), but the food consumption of toddlers in the highlands was more diverse than in the coastal area (p<0.05). Conclusion: Mothers in the highlands generally have a higher level of education than mothers on the coastal and so was the household income. The number of households in the highlands with food secure was higher than in the coastal but it was not significantly different. And children's food consumption is more diverse in the highlands than in the coastal. KEYWORDS: Coastal, Food Security, Highlands, Nutritional Status, Toddler.